Prevalence of HPV Infection and High Risk HPV Genotypes (16, 18), among Monogamous and Polygamous Women, In Zabol, Iran - I Shahramian; Z Heidari; HR Mahmoudzadeh-Sagheb; A Moradi; F Forghani (Tehran University of Medical Sciences, 2011)
Background: This study was performed to compare the prevalence of HPV infection and high risk HPV genotypes [16, 18] between monogamous and polygamous women, in Zabol, Iran.Methods: This cross sectional study was conducted in Zabol in 2006 - 2007. Two hundred sixty five married women attending the Gynecology Clinic for Cervical Disease Screening entered to this study. One hundred sixty two cases had monogamous, and 103 had polygamous husbands. HPV PCR samples were obtained from scrape of papsmear specimens. The biotinylated primers MY09/MY11, GP5+/GP6+, were utilized to enable amplification and detection of positive PCR products. Confirmation of HPV-16 and -18 were done by type-specific PCR primers HPV-16/F, HPV-16/R and HPV-18/F, HPV-18/R.Results: Prevalence of HPV infection in monogamous and polygamous groups was 29% and 37.9%, respectively. The most HPV infection was found in 15-25 years group. The most prevalence of infection in monogamous group was HPV-18 and HPV- non16, 18 in 15-25 years, and HPV-16 in 26-35 years group. In polygamous group the most prevalent type was HPV-16, 18 in 15-25 years group. The most prevalent HPV-16 was seen in sever inflammation and dysplasia cytology in both groups.Conclusion: Prevalence of HPV infection in Zabol is high, and in women with polygamous husbands group is slightly more than monogamous. Screening for this infection must be recommended in this region of Iran.